Children's longitudinal bodyweight in Australia: Influence of migrant mothers' long-term residency, attachment to, and level of childhood overweight in country-of-birth - Hartono, Susan; Cochrane, Tom; Niyonsenga, Theo; Kinfu, Yohannes (My University, 2022)
Immigration creates opportunities and imposes constraints associated with acculturation. We used the Australian national longitudinal survey of children aged 2 to 17 to evaluate the influence of mothers' long-term residency in Australia, mothers' attachment to country-of-birth, and macro indicators of childhood overweight environment at mothers' country-of-birth on children's longitudinal bodyweight. Both mothers' long-term exposure to the Australian environment and attachment to country-of-birth were associated with increased children's bodyweight z-scores. The childhood overweight environment in mothers' country-of-birth continued to influence their children's bodyweight after immigration. A better understanding of factors related to mothers' migration and children's bodyweight status is necessary to identify risk factors and migrant sub-groups needing extra support.
Keywords: Childhood and child development; Health and wellbeing; Migration and settlement